Growth pattern of stock cultures of five selected species of marine microalgae maintained under indoor controlled environment and under outdoor conditions - Ajithkumar, P. B.; Joseph, Shoji; Vidya, K. (Indian Journal of Fisheries, 2019)
Growth pattern of five species of microalgae viz., Chaetoceros calcitrans, Dunaliella sp., Isochrysis galbana, Tetraselmis tetrahele and Nannochloropsis salina were studied under indoor controlled conditions (at 230C) and under outdoor (at 28-30Â°C) conditions. The variations in ammonia and pH levels in the culture flasks over a period of 90 days were also studied. Results revealed that the pattern of growth of all five species of algae were significantly different (p